Finding Solutions to Productive Waqf Management Problems: A Case in Indonesia - Hakim, Lukman; Nawawi, Kholil (International Journal of Waqf, 2024)
Poverty is now a multifaceted problem as it is related to the inability to access and participate in society economically, socially, culturally and politically. According to the Indonesian Waqf Agency (BWI), Indonesia, which has the world's largest Muslim population, has great potential for waqf money estimated at Rp. 1.4 trillion as of March 2022, this figure has increased when compared to the waqf money that has been collected in the 2018-2021 period of Rp. 855 billion. With a very large Muslim population and high potential for raising waqf funds, waqf in Indonesia has enormous potential as an instrument of development and poverty alleviation. Waqf can contribute to a country's economic development, It can reduce government spending, equalize income distribution, reduce poverty, and boost economic growth. Additionally, waqf has the potential to improve people's health. Essentially, the waqf should be productive as stated in the hadith. but the latest based on research results in the management process at PT Karya Mandiri Community (KMM) Parung has 2 main problems, namely human resource problems and institutional problems. The problem of human resources is divided into three aspects, namely, Nazhir's managerial ability is relatively low, Nazhir is less creative, and people's understanding is still traditional. While institutional problems, namely coordination between the PT KMM and the community is relatively low. This study focuses on problem solving analysis of productive waqf management issues carried out by PT KMM.